The Influence of Rheological Properties on The Pump Power Requirement for Transfering Ketchup - Darwin Darwin (Department of Agricultural Engineering, Syiah Kuala University, 2013)
Abstract. This research aimed to analyze the influence of rheological properties of ketchup on the pump power, required during transporting process. This research was done through using a computer programme designed for calculating and analyzing the influence of rheological properties toward materials and equipments installed in the transport system. Those rheological properties derived from laboratory analysis and literature review include viscosity and density from any type of ketchup. Results analysed by a computer programming revealed that flow behaviour Index (n) and consistency coefficient (m) were the rheological properties interacting with each other since these parameters were the viscosity of ketchup that influences energy losses in the transport system. Once the total of energy losses was obtained from the system, the pump power required for transfering the product also can be known. Based on the simulation conducted by using rheological parameters of ketchup with consistency coefficient of 12.33 PaSn, and flow behaviour Index at 0.41 was obtained total energy losses at 202.26 J/kg with the pump power requirement at 0.22 kW. Once consistency coefficient was 18.7 PaSn, and flow behaviour Index was at around 0.4, the total of energy losses increased to 277.58 J/kg with pump power requirement at 0.28 kW. Abstrak. Penelitian ini bertujuan untuk menganalisa pengaruh dari sifa-sifat reologi dari kecap terhadap daya pompa yang dibutuhkan selama proses transfer atau pengalirannya. Penelitian ini dilakukan menggunakan suatu program komputer yang didesain untuk menghitung dan menganalisa pengaruh sifat-sifat reologi terhadap peralatan dan bahan yang digunakan pada sistem transfer. Sifat-sifat reologi tersebut diperoleh dari analisis laboratorium dan studi literatur yang berupa viskositas dan densitas dari berbagai tipe kecap. Hasil yang telah dianalisis dengan program komputer mengungkapkan bahwa index perilaku aliran (n) dan koefisien konsistensi (m) merupakan sifat reologi bahan yang saling berinteraksi, hal ini karena parameter tersebut merupakan viskositas dari kecap yang mempengaruhi kehilangan energi pada sistem transfer. Ketika total kehilangan energi dari sistem diketahui, maka daya pompa yang dibutuhkan untuk mentransferkan produk kecap tersebut juga dapat diketahui. Berdasarkan simulasi yang dilakukan dengan menggunakan parameter-parameter reologi dari kecap dengan koefisien konsistensi 12.33 PaSndan index perilaku aliran 0.41 maka diperoleh total kehilangan energi sebesar 202.26 J/kg, daya pompa yang dibutuhkan sebesar 0.22 kW. Ketika koefisien konsistensi bahan 18.7 PaSn, dan index perilaku aliran 0.4, maka total kehilangan energi meningkat menjadi 277.58 J/kg dengan daya pompa yang dibutuhkan juga meningkat menjadi 0.28 kW.